EFEKTIVITAS E-MODUL DALAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PERENCANAAN KARIR SISWA - Ikbal Abdul Malik; Ecep Supriatna; Tuti Alawiyah (IKIP Siliwangi, 2023)
This research is motivated by the lack of career planning that occurs in high school / MA students. Whereas career planning is a very important and important part for students to maximize their potential during learning activities. The research objective is to develop an E-Module media in group guidance to help students' career planning. This study uses quantitative research methods. This study is a pre-experimental design research using a one group pretest-posttest design because this design is designed to compare a treatment. The subjects in this study were students of SMA Al-Amanah Ciwidey, totaling 30 students. The analysis used is the Paired Sample T-Test formula. Based on the results of the research, it shows that group guidance with the use of E-Modules can improve students' career planning which can be seen from the significant difference from the average before group guidance of 72 and after group guidance of 83. The conclusion in this study is that group guidance using E media -The module can improve career planning for students of class XI Al-Amanah Ciwidey.